UNCOVERING THE CHALLENGES FACED BY HIGH SCHOOL STUDENTS IN SPEAKING ACTIVITIES THROUGH LEGEND STORY ROLEPLAY - Gema Ramadhan, Hillal; Tauhidin Abas, Totoh; Fitriyana, Wahyudin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to explore the challenges faced by 10th-grade high school students in English speaking activities through legend story-based roleplay. The study used a descriptive qualitative approach involving 10th-grade students who have participated in legend story roleplay activities. Data were collected through semi-structured interviews and analyzed using the interactive analysis model of Miles (2014), which includes data condensation, data display, and drawing conclusions. The results show that students face several main challenges, such as limited vocabulary, pronunciation difficulties, speaking anxiety, difficulties in acting out characters, and obstacles in group cooperation. Limited vocabulary and pronunciation are the main challenges because they affect students' ability to deliver dialogues smoothly and confidently. Despite this, students respond positively to using legend-based roleplay because it is considered interesting, fun, and helps them practice speaking in a more meaningful context. Besides improving speaking skills, this activity also introduces local cultural values through legend stories. The findings of this study suggest that legend-based roleplay has potential as an effective learning strategy, provided that teachers give enough support to help students overcome the various challenges they face.